New insight on macrolide antibiotics - Goździk, Joanna (Przewodnik Lekarza/Guide for GPs, 2010)
Macrolides are antibiotics commonly use in respiratory system infection. They have broad spectrum of antibacterial activity against Gram-positive, Gram-negative and atypical pathogens. Macrolid therapy has also anti-inflammatory properties, beneficial effects on the immune system in the course of chronic inflammation. This review presents the evidence for their long-term use as anti-inflammatory agents in asthma and cystic fibrosis, two respiratory diseases characterized by chronic inflammation, leading to remodellig of the airways.